Investigating the use of vague language as a communicative strategy in Chinese business negotiations - Zhao, Xiaohua (Curtin University, 2010)
Chinese has long been perceived as being a hánxù (‘inscrutable’) language with indirect ways of communicating. This study aims to investigate indirectness in Chinese communication by exploring the use of vague language as a communicative strategy in Chinese business negotiations where vagueness plays a vital role in the communicative process. Vague language in this study is defined as inexplicit expressions used strategically, exemplified by diǎnr/yīdiǎnr (‘a little’), kěnéng (‘possibly’), dàyuē (‘about’), hěnduō (‘many’), and jīngcháng (‘often’), etc. It should not be confused with ‘misused language’. On the contrary, it is an integral part of the language and is indispensable in communication. This is one of the first attempts to study the use of vague language in real-life Chinese business negotiations, providing insights into the vagueness in Chinese language and developing possible models for effective communication in Chinese business discourse.This research is conducted by examining linguistic representations of vague language as they occur naturally in Chinese business negotiations. Through investigating the roles vague language plays in the real-life data with salient characteristics of inexplicitness, and its socio-cultural features, the research holistically addresses the questions of what lexical and syntactic patterns of vague language are frequently used in Chinese business negotiations, how negotiators interact in the realization of vagueness using sequential patterns, and what the pragmatic and cultural reasons for the use of vague language are.It is concluded that being communicative strategies, vague expressions should be as, or more, conventional and effective as non-vague expressions. Very often they may be preferable to non-vague expressions, because of their greater efficiency and relevance. The findings in this study are that while vague language is used for a combination of practical and interpersonal purposes, the priority is the practical functions. The ways in which it is mobilised are, in different shapes and forms and to lesser or greater degree, influenced by the social factors of age, social distance and gender. The findings of this study add an important dimension to the study of vague language and also have implications for the exploration of effective communication in general.